(untitled) (Research, Society and Development, 2020)
The yellow passionfruit (Passiflora edulis Sims f. flavicarcarpa Deg.) is important culture in Brazilian Amazon agriculture, especially in the state of Pará. But its cultivation has been suffering the reduction of its areas and productivity due the diseases caused by bacteria, where chemical control, sometimes does not present the expected results. The propolis of Africanized bees (Apis mellifera L.) is an important natural antibiotic for the control of undesirable microorganisms of plants and animals. The present work aimed at the in vitro study of the antibiotic activity of different propolis extracts of Africanized bees from two different locations in the state of Pará in the agent that causes the passionfruit bacterial blight (Xanthomonas axonopodis pv. passiflorae). A factorial analysis of three factors was performed: origin X solvent X concentration. It was verified that the concentrations of 0.5% were statistically superior to the others, with average growth inhibition power of 86%, and the propolis extract from an apiary in Santa Izabel do Pará, Pará, Brazil, obtained in ethanol at 80%, was statistically different and superior for the inhibitory effect of the growth of colony forming units (CFU) of X. axonopodis pv. passiflorae.